ATTRIBUTION OF THE CONCEPT “MEMORY” IN M. TSVETAEVA’S TEXTS (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-44-51Abstract. The study deals with the problems of attributive representation of the concept “memory” in M. Tsvetaeva’s texts. The article carries out the results of cognitive-semantic analysis of epithet word usages of memory in the poet’s texts and the Dictionary of Epithets of the Russian Literary Language. It has been established that M. Tsvetaeva’s individual style is characterized by the construction of occasional epithets, a violation of the lexical compatibility of customary definitions with the defined word “memory”. It shows that the specificity of the attribution of this concept is associated with individual emotive connotations, which is expressed in a non-standard epithet expression of the qualities of the concept “memory” and its manifestations.Key words: epithet, Marina Tsvetaeva, concept, individual style, epithet complex, epithet paradigm